Performance analysis of selected database systems: MySQL, MS SQL, PostgerSQL in the context of web applications - Lachewicz, Katarzyna (Journal of Computer Sciences Institute, 2020)
The main purpose of this article is to check which database: MySQL, MS SQL, PostgerSQL is the most efficient for Internet applications. This work contains information about the databases used, but the most important part of this article is database performance research. They are based on an application whose main task was database queries. The program was created based on new technologies, such as the Spring framework, the Hibernate library and JDBC Interface.